The Influence of Work Environment and Perceived Organizational Support on the Employee Performance of PT Y in Surabaya with Employee Engagement as an Intervening Variable - Audina Anggraini; Hermien Tridayanti; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the influence of work environment and perceived organizational support on the employee’s performance of PT Y in Surabaya, both directly or indirectly with employee engagement as an intervening variable. This research is a quantitative study. Population and sample based on the distribution of questionnaires to the performance of the employees of PT Y in Surabaya was taken as many as 30 respondents. Data collection techniques used interviews, observations, and questionnaires. For statistical tests and the processing of data is carried out by using the partial least square (Smart PLS 3.0). The study showed that each variable, work environment and perceived organizational support had a direct significant influence on employee performance and employee engagement. Work environment had a direct significant effect on employee performance with a t-statistical value of 2.136 greater than the indirect effect through employee engagement as an intervening variable with a t-statistics value of 1.454. While perceived organizational support had a direct effect on employee performance with t-statistics of 2.550 is greater when compared to the indirect effect through employee engagement as an intervening variable with t-statistics 2.042.